2018
DOI: 10.1051/shsconf/20185402001
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Workers’ Village as an Effort to Strengthen The Rights of Indonesian Migrant Workers

Abstract: Many problems faced by Indonesian migrant workers and a comprehensive protection are the reason for the government to ratify Law No. 18 year 2017, The Protection of Indonesian Migrant Workers. The regulation provides protection by not only the central government, local government but also village government. It is expected to provide protection in pre-departure stage, during or after placement. The existence of village of migrant workers which has protection for migrant workers by: doing procedural administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These networks are not only among migrant workers but also among the families or associations of migrant workers in Indonesia. The social capital in the form of networks owned by migrant workers is the main capital in social interaction and communication (Anggaunitakiranantika, 2016;Rahayu, 2018).…”
Section: Social Capital For Indonesian Migrant Workers In Hong Kongmentioning
confidence: 99%
See 1 more Smart Citation
“…These networks are not only among migrant workers but also among the families or associations of migrant workers in Indonesia. The social capital in the form of networks owned by migrant workers is the main capital in social interaction and communication (Anggaunitakiranantika, 2016;Rahayu, 2018).…”
Section: Social Capital For Indonesian Migrant Workers In Hong Kongmentioning
confidence: 99%
“…According to the research results conducted Wulan (2011 This is intended to maintain sustainability, both in terms of communication and social interaction between migrant workers who have left Indonesia and their regions of origin. In addition, another research found that building overall community awareness is also needed as a stakeholder interest to protect the migrant workers and their families (Rahayu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…NGOs also work with potential migrant workers, while they are in their country of origin and also protect migrant workers who are employed overseas (Rahayu, 2018). NGOs, in country of origin, "focuses on policy advocacy and servicing to strengthen legal protection for migrants" and often work with other NGOs in country of destination, which focuses on the same issues and provide similar services (Ford, 2019).…”
Section: Lessons From Ngos In South East Asia That Work With Migrant ...mentioning
confidence: 99%
“…NGOs, in country of origin, "focuses on policy advocacy and servicing to strengthen legal protection for migrants" and often work with other NGOs in country of destination, which focuses on the same issues and provide similar services (Ford, 2019). In Indonesia, NGOs such as Solidaritas Perempuan and Centre for Indonesian Migrant Workers, focuses on strengthening the rights of migrants by helping them study the regulations of the destination country, conducting socializing events to learn from migrants who have returned back to Indonesia, and understanding their rights and rules in case they experience any problem (Rahayu, 2018). Indonesian migrant workers, especially FMW, receive very low wages because villages in Central and East Java, with the help and support of Migrant Care (Rahayu, 2018).…”
Section: Lessons From Ngos In South East Asia That Work With Migrant ...mentioning
confidence: 99%